Investigating the Relationship between Teacher Resilience, Teacher Immunity and Emotional Intelligence among Iranian EFL Teachers - Fahimeh Rezapoor; Aysheh Mohammadzadeh (Research in English Language Pedagogy, 2024)
Teacher resilience and teacher immunity are important qualities which are of high significance in today’s scope of EFL teacher education and teacher psychology. The present study explored whether there are any correlations or associations between teacher resilience, teacher immunity and emotional intelligence among Iranian EFL teachers. So, 90 EFL teachers from different English language institutes in Gorgan, Iran were chosen through convenience sampling procedure. To collect the data, three instruments: Teacher Resilience Questionnaire, Language Teacher Immunity Questionnaire, and Emotional Intelligence Questionnaire were used. The correlation test, Pearson, was run in order to examine the relationship between teacher emotional intelligence and teacher immunity, teacher emotional intelligence and teacher resilience and the relationship between teacher immunity and teacher resilience. The results indicated a significant relationship between Iranian EFL teachers’ emotional intelligence and teacher immunity. In addition, findings revealed a positive relationship between emotional intelligence and teacher resilience too and also a positive and significant relationship between teacher immunity and teacher resilience as well. As pedagogical implications, teachers who suffer from lower resilience and immunity should be informed on various ways of improving them including increasing their practicing on emotional intelligence.